Frequent gain and loss of introns in fungal cytochrome b genes. - Liang-Fen Yin; Meng-Jun Hu; Fei Wang; Hanhui Kuang; Yu Zhang; Guido Schnabel; Guo-Qing Li; Chao-Xi Luo (PLoS ONE, 2012)
In this study, all available cytochrome b (Cyt b) genes from the GOBASE database were compiled and the evolutionary dynamics of the Cyt b gene introns was assessed. Cyt b gene introns were frequently present in the fungal kingdom and some lower plants, but generally absent or rare in Chromista, Protozoa, and Animalia. Fungal Cyt b introns were found at 35 positions in Cyt b genes and the number of introns varied at individual positions from a single representative to 32 different introns at position 131, showing a wide and patchy distribution. Many homologous introns were present at the same position in distantly related species but absent in closely related species, suggesting that introns of the Cyt b genes were frequently lost. On the other hand, highly similar intron sequences were observed in some distantly related species rather than in closely related species, suggesting that these introns were gained independently, likely through lateral transfers. The intron loss-and-gain events could be mediated by transpositions that might have occurred between nuclear and mitochondria. Southern hybridization analysis confirmed that some introns contained repetitive sequences and might be transposable elements. An intron gain in Botryotinia fuckeliana prevented the development of QoI fungicide resistance, suggesting that intron loss-and-gain events were not necessarily beneficial to their host organisms.